2016
DOI: 10.1177/1933719115592707
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension in an Animal Model of HELLP Syndrome is Associated With Activation of Endothelin 1

Abstract: Women with hypertensive forms of pregnancy such as hemolysis-elevated liver enzymes-low platelet syndrome have increased circulating endothelin 1; however, the relationship between hypertension and endothelin 1 has not been studied. Using an animal model, we sought to determine whether there was an increased activation/dysfunction of endothelin 1, the effect of endothelin 1 receptor-A blockade on hypertension and other manifestations of hemolysis, elevated liver enzymes, and low platelets syndrome. On gestatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
40
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 49 publications
3
40
0
Order By: Relevance
“…It is possible that in severe PE and in HELLP syndrome the production of ET-1 is so augmented that ET-1 release “loses” its paracrine directionality and consequently an increase in circulating ET-1 levels is detected. This is supported by reports that rat models that mimic severe PE and HELPP syndrome have increased plasma ET-1 levels (Johnson et al, 2014; Morris et al, 2015) (Table 2). …”
Section: Increased Endothelium-derived Contracting Factors In Preesupporting
confidence: 74%
See 1 more Smart Citation
“…It is possible that in severe PE and in HELLP syndrome the production of ET-1 is so augmented that ET-1 release “loses” its paracrine directionality and consequently an increase in circulating ET-1 levels is detected. This is supported by reports that rat models that mimic severe PE and HELPP syndrome have increased plasma ET-1 levels (Johnson et al, 2014; Morris et al, 2015) (Table 2). …”
Section: Increased Endothelium-derived Contracting Factors In Preesupporting
confidence: 74%
“…sEng may act in concert with sFlt-1 to induce vascular permeability, proteinuria, IUGR and severe HTN in pregnant rats (Venkatesha et al, 2006). Pregnant rats infused with both sFlt-1 and sEng via mini-osmotic pump show HELLP syndrome-like features (Morris et al, 2015). Also, sEng impairs the formation of endothelial tubes in cultured HUVECs (Venkatesha et al, 2006).…”
Section: Circulating Bioactive Factors In Preeclampsiamentioning
confidence: 99%
“…The levels of sEng are higher in preeclampsia and the hemolysis, elevated liver enzymes, and low platelets (HELLP) syndrome compared with normal pregnant women [21, 88], and the serum and placenta levels of sEng are increased while serum TGF-β levels are decreased in RUPP rats [61]. When co-administered with sFlt-1 in pregnant rats, sEng induces vascular permeability, proteinuria, IUGR, severe HTN-Preg and HELLP syndrome-like features [89]. The expression of sEng is increased in placental explants exposed to hypoxia [90], and sEng impairs tube formation in human umbilical vein endothelial cells (HUVECs) [88].…”
Section: Discussionmentioning
confidence: 99%
“…Infusion or overexpression of sFlt-1 and sEng into normal pregnant rats leads to a HELLP like phenotype in the recipient rats. This phenotype is expressed not only by the increase in hemolysis, elevated liver enzymes and decreased platelets, but also by a significant increase in mean arterial pressure, inflammatory cytokines, endothelin-1, CD4 + and CD8 + T lymphocytes 810 . A substantial number of studies have demonstrated that systemic inflammation mediated by inflammatory cytokines, anti-angiogenic growth factors, CD4 + T cells, or the damaged vascular endothelium can impair the BBB 1113 .…”
Section: Introductionmentioning
confidence: 99%
“…However, CD8 + T cells are associated with neuroinflammatory conditions such as neurological paraneoplastic syndromes and multiple sclerosis 15, 16 . As CD4 + and CD8 + T cells are increased in response to infusion of sFlt-1 and sEng 9, 10 we sought to determine if 1) rats with HELLP syndrome had an increase in BBB permeability and 2) if T cells contributed to the inflammation and any potential increase in BBB permeability in an animal model of HELLP syndrome.…”
Section: Introductionmentioning
confidence: 99%